Diabetic Gastroparesis: Epidemiology, Pathophysiology, Symptoms, and Clinical Consequences - Olgierd Dróżdż; Piotr Gacka; Marcin Dołęga; Dominika Musialska; Maciej Rabczyński; Joanna Gołda; Julia Mężyk; Aleksandra Snopkowska (Nicolaus Copernicus University in Toruń, 2024)
Diabetes mellitus affects over half a billion people worldwide and is associated with numerous complications, including diabetic gastroparesis, characterized by delayed gastric emptying without mechanical obstruction. Although diabetic gastroparesis does not affect life expectancy, it significantly impairs digestion and medication absorption, complicating glucose metabolism and health management, thus reducing quality of life. The etiology of diabetic gastroparesis is multifactorial, involving autonomic neuropathy, vagus nerve dysfunction, disturbances in interstitial cells of Cajal, nitric oxide synthesis, hyperglycemia, and oxidative stress. Symptoms include early satiety, bloating, nausea, vomiting, dysphagia, and unintentional weight loss, which complicate diabetes management by causing unpredictable glycemic control. Despite advancements in understanding diabetic gastroparesis, it remains underdiagnosed due to its often asymptomatic nature. Further research is needed to elucidate its epidemiology and pathophysiology, particularly in asymptomatic patients. This review discusses the epidemiology, pathophysiology, symptoms, and clinical consequences of diabetic gastroparesis, highlighting the need for improved diagnostic and management strategies.